Palm Oil Zakat from a Contemporary Fiqh Perspective: A Comparative Study of Fatwa from the Aceh Ulema Consultative Assembly (MPU) and the Indonesian Ulema Council (MUI) - Azmiadi Azmiadi; Hayati Hayati; Abdul Manan; M Chalis; Muliadi Muliadi (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
This research is motivated by the high economic contribution of the palm oil plantation sector in Indonesia and Aceh Province, which empirically triggers contemporary legal debate due to the absence of explicit mention of the commodity in classical religious texts. The purpose of this research is to analyze the foundations of contemporary fiqh, compare technical provisions (nishab, haul, and kadar), and examine the theoretical and practical implications of the dualism of fatwa between the Indonesian Ulema Council (MUI) and the Aceh Ulema Consultative Assembly (MPU). The method used is a normative Islamic legal research with a qualitative approach based on library research through content analysis and comparative analysis techniques. Primary data sources come from MUI Fatwa Number 3 of 2003 and MPU Aceh Fatwa Number 9 of 2013, supported by secondary data in the form of zakat fiqh literature, scientific journals, and official statistical data. The main findings of this research explore the epistemological dialectic between the Shafi'i school of thought approach based on illat al-qut wa al-iddikhar and contextual reasoning based on illat al-nama' wa al-kasb. The theoretical significance of this competing paradigm enriches contemporary Islamic legal studies in reconstructing the dynamic economic functionality of public property. The formulation of a harmonization model for palm oil zakat offers a significant contribution by separating the management of small-scale community palm oil plantations from corporate palm oil. Regular integration of this model into the technical regulations of Baitul Mal Aceh and BAZNAS has the potential to support efforts to bridge differences in the fatwa authority, provide alternative legal certainty for zakat payers, and optimize the sustainable distribution of wealth for mustahik (recipients of zakat).